2017
DOI: 10.1371/journal.pone.0170793
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Database Forensic Metamodel (DBFM)

Abstract: Database Forensics (DBF) is a widespread area of knowledge. It has many complex features and is well known amongst database investigators and practitioners. Several models and frameworks have been created specifically to allow knowledge-sharing and effective DBF activities. However, these are often narrow in focus and address specified database incident types. We have analysed 60 such models in an attempt to uncover how numerous DBF activities are really public even when the actions vary. We then generate a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…The second approach is based on Model Based Systems Engineering (MBSE). This approach facilitates systems engineering activities through development of standard and integrated models which provides a common understanding and results in enhanced communications (Friedenthal, Moore, & Steiner, 2009) (Othman & Beydoun, 2016) (Al-dhaqm et al, 2017. MBSE "is the formalized application of modelling to support system requirements, design, analysis, verification, and validation activities beginning in the conceptual design phase and continuing throughout development and later life cycle phases" (SE Handbook Working Group, 2011).…”
Section: Background and Related Workmentioning
confidence: 99%
“…The second approach is based on Model Based Systems Engineering (MBSE). This approach facilitates systems engineering activities through development of standard and integrated models which provides a common understanding and results in enhanced communications (Friedenthal, Moore, & Steiner, 2009) (Othman & Beydoun, 2016) (Al-dhaqm et al, 2017. MBSE "is the formalized application of modelling to support system requirements, design, analysis, verification, and validation activities beginning in the conceptual design phase and continuing throughout development and later life cycle phases" (SE Handbook Working Group, 2011).…”
Section: Background and Related Workmentioning
confidence: 99%
“…However, we discuss how the existing literature utilizes each attributes to solve the issues raised in APLS. This study adopted the meta-modeling creation process [17] for designing the learner model. The method contains the process of modeling various models (meta-modeling) to standardize and reuse the available models.…”
Section: Methodsmentioning
confidence: 99%
“…Model selection for this research will be based on coverage factors that were identified in previous research (Al-dhaqm et al, 2017;Ali et al, 2017;Kelly and Pohjonen, 2009;Othman et al, 2014). A wide coverage of viewpoints, concepts, and terminologies that are broadly applicable will be required to fulfill the aim of identifying and proposing common concepts SCM practices in oil and gas sector.…”
Section: Phase 2: Identify Investigate and Evaluate The Main Conceptsmentioning
confidence: 99%
“…The extracted SCM concepts in oil and gas sector are merged and grouped together based on similar activities and concepts (Al-dhaqm et al, 2017). All concepts having similar activities and meaning are organized, merged and grouped into separate groups.…”
Section: Phase 2: Identify Investigate and Evaluate The Main Conceptsmentioning
confidence: 99%